Chapter 12: Statutory Interpretation - GOH, Yihan (Institutional Knowledge at Singapore Management University, 2015)
The importance of statutory interpretation canno be overstated. While Singapore is a common law system, its lwas also comprise statutes. Each statue must be interpreted and then applied to the case at hand. The theory and practice of interpreting statutes is the law of statutory interpretation.